Design and testing of a semi-active inerter with magneto-rheological fluid valve. (14th September 2021) - Yu, Jianqiang; Dong, Xiaomin; Su, Xi; Tao, Xiangyuan; Li, Xin
Abstract: This paper presents a novel semi-active inerter with magneto-rheological fluid valve (SAI-MRFV) for improving semi-active system performances in low-frequency domain. The proposed device is composed of a driver element and two driven elements. Driven element 1 contains a hydraulic motor and a plate. Driven element 2 contains a cylinder, two piston rods, two floating pistons and a MR valve. The two driven elements are connected in parallel. The area between the floating pistons is filled with MR fluid, while other areas of SAI-MRFV are filled with hydraulic oil. With the motion of driver piston, the hydraulic oil will be circulated in driver element and driven elements. The flow rate distribution of hydraulic oil in two driven elements can be changed by controlling the pressure drop of driven element 2. Along with the changing of the hydraulic oil flow rate in hydraulic motor, the inertance and damping can be tuned simultaneously. A novel compact annular-radial-orifice flow MR valve is proposed to provide controllable pressure drop in driven element 2. Besides, a theoretical model was established to describe the characteristics of variable inertance and damping force. Based on the conceptual design and theoretical analysis, a prototype was designed, fabricated and tested. The characteristics of single inerter, single MR valve and SAI-MRFV were obtained by a series of experimental tests. The experimental results show that the inertance and damping can be controlled by the changing current of MR valve.